URGENT ISSUES OF SOCIAL PEDIATRY IN RUSSIA - L.P. Chicherin ("Paediatrician" Publishers LLC, 2006)
The article highlights the issues of social pediatry, arising from events aimed at preservation and promotion of health, prevention of diseases among children and teenagers at the outpatient level. Based on the findings of the lasting research, the authors described the state of social pediatry in the beginning of the 21st century. They examined the activity of medical and social care departments as new units of the children's outpatient hospitals. Special chapter is dedicated to the implementation of general practice and family practice principles into the activity of medical and preventive treatment facilities of the primary chain within the pediatric service.Key words: social pediatry, public health organization, formation of pediatric service, child welfare.